Untying the Influence of Green Brand Authenticity on Electronic Word-of-Mouth Intention: A Moderation–Mediation Model - Xu, Yuhuan; Du, Jianguo; Shahzad, Fakhar; Li, Xingwei (Frontiers in Psychology, 2021)
Green brands have made considerable strides in recent years, however, their validity has been questioned due to green brand fraud. However, the influence of green brand authenticity on consumer online behavior is still lacking in the e-commerce boom era. This article presents a theoretical framework based on trust and self-determination theory to investigate the influence of green brand authenticity on electronic word-of-mouth. The conclusions are drawn from an empirical examination of 292 valid responses. Green brand authenticity influences electronic word-of-mouth intent, which is mediated through brand trust. Self-concept consistency has a moderating effect on the relationship between green brand authenticity and brand trust. The findings paved the way for future green brand development, notably in terms of publicity and promotion. This article also describes its theoretical and management significance, limitations, and future research directions.